1997
DOI: 10.1590/s0004-282x1997000500002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cranial nerves of rats inoculated with rabies virus

Abstract: The V and VII cranial nerves of rats inoculated with rabies virus were studied by electron microscopy. The results were compared with the same cranial nerves of rats inoculated with rabies virus but vaccinated against the disease. The findings are those of axonal degeneration and intense demyelination of the nerves of the group of rats not vaccinated. The vaccinated rats showed some ultrastructural irrelevant alterations when compared with the other group. The degree of ultrastructural alterations found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Wallerian degeneration refers to a process that results when part of the axon degenerates in isolation of changes in the neuronal cell body. Minguetti and colleagues reported axonal degeneration and demyelination in both peripheral and cranial nerves of rodents inoculated with RV (181,182). Examination of mouse sciatic nerves inoculated with RV revealed that axonal degeneration mainly occurred in myelinated axons (183).…”
Section: Axonal Damage and Degenerationmentioning
confidence: 99%
“…Wallerian degeneration refers to a process that results when part of the axon degenerates in isolation of changes in the neuronal cell body. Minguetti and colleagues reported axonal degeneration and demyelination in both peripheral and cranial nerves of rodents inoculated with RV (181,182). Examination of mouse sciatic nerves inoculated with RV revealed that axonal degeneration mainly occurred in myelinated axons (183).…”
Section: Axonal Damage and Degenerationmentioning
confidence: 99%
“…Although axonal transport of virus can lead to axonal degeneration [53], neuronal infection and axonal transport of virus may not result in axonal injury. A recombinant virus vector has been shown to be axonally transported in neurons without tissue damage [13].…”
Section: Axonal Pathology In Virus Infectionmentioning
confidence: 99%
“…Different virus families (Herpesviridae, Rhabdoviridae, Flaviviridae, Bornaviridae and Picornaviridae) include important human neurotropic viruses, such as herpes simplex virus, rabies virus, West Nile virus, poliovirus and others [8]. Neurotropic viruses often cause apoptosis of neurons [7,9,10] and axonal degeneration [11], which results in death of hosts or permanent neurological deficits [12]. For example, both poliovirus and West Nile virus have been shown to cause apoptosis of neurons [9,13,14] and axonal degeneration [15,16] in the CNS.…”
mentioning
confidence: 99%